Some Things Are Rarely Discussed in Public - on the Discourse of Corruption in Healthcare; Comment on "We Need to Talk About Corruption in Health Systems" - Peter Stiernstedt (Kerman University of Medical Sciences, 2019)
In an editorial titled "We Need to Talk About Corruption in Health Systems" the authors Hutchinson, Balabanova, and McKee hope to encourage a wider conversation about corruption in the health sector. Such conversations are difficult to hold for at least five reasons; it is hard to define corruption; corruption may allow some fragile health systems to subsist, shifting blame - are those involved in anti-corruption research colluding with corrupt officials; the legitimacy of studying corruption; and, that far too little is known about how to tackle corruption. This commentary explores those reasons and concludes that the authors make a strong case for a more open and directed discussion about corruption.